Electronically Tunable Wide Band Optical Delay Line Based on InGaAs Quantum Well Microresonators. (5th September 2013) - Zhang, Yan; Taylor, Geoff W.
Abstract : A novel electronically tunable optical delay line based on InGaAs quantum well microresonators is proposed for high frequency RF transmission. The device utilizes the charge-controlled blue shift of the absorption edge in InGaAs quantum wells to change the effective refractive indices of the resonators and couplers, therefore, provides an efficient way to produce variable time delay. A theoretical model based on measurements is used to analyze the device performance. Simulation results for five 3 × 27  μ m 2 cascaded resonators with bias voltages <0.7 V show a continuous tuning range of 7~68 ps, a ripple delay <1.5 ps, and a useable bandwidth of 39.3 GHz.